(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: A cross-sectional study was conducted to reveal the hematology, serum biochemistry, and reproductive behavior of free-roaming cats in the Sylhet Division of Bangladesh. Materials and Methods: Overall, 130 free-roaming cats were captured, of which 52 were Tom (male), 69 were Queen (female), and 9 were kittens. Regarding their ages, the cats were divided into three groups: <1 year as kittens, 1 to 2 years as young, and adults over two years. Thirty blood samples were drawn from the cephalic or saphenous veins of the hind leg for hematological and serum biochemical analysis. Results: The findings revealed that the average hemoglobin concentration was significantly higher in kittens than in young and adult cats (p <1 year as kittens, 1 to 2 years as young, and adults over two years. Thirty blood samples were drawn from the cephalic or saphenous veins of the hind leg for hematological and serum biochemical analysis. Results: The findings revealed that the average hemoglobin concentration was significantly higher in kittens than in young and adult cats (p >< 0.05). In comparison to young and adult cats, kittens had considerably greater red blood cell, packed cell volume, mean corpuscular volume, and platelet counts, whereas mature cats had much higher white blood cell counts. The number of lymphocytes and monocytes was shown to be non-significant, while other components, such as neutrophils, eosinophils, and basophils, varied considerably by age group. Rural cats showed significantly (p < 0.05) higher alanine transaminase and aspartate aminotransferase, whereas urban cats showed higher serum glucose (p < 0.001). The duration of the cat’s estrous cycle was (5.63 ± 1.75) days, as were the inter-estrous phase’s length (7 days), gestation time (66.6 days), and queening rate (65.2). There were 3.92 ± 0.55 kittens per litter. Males reached puberty at a young age of 9.3 months, while females did so at 8.3 months. Conclusion: These findings may contribute to the growing body of research on free-roaming cat populations, which is important for understanding the ecology and behavior of these cats and constructing strategies for their conservation and welfare. J. Adv. Vet. Anim. Res., 12(1): 70–79, March 2025 http://doi.org/10.5455/javar.2025.l873